Prognostic and therapeutic value of disruptor of telomeric silencing-1-like (DOT1L) expression in patients with ovarian cancer - Xiaoxue Zhang (Journal of Hematology & Oncology, 2017)
Abstract Background Epigenetics has been known to play a critical role in regulating the malignant phenotype. This study was designed to examine the expression of DOT1L (histone 3 lysine 79 methyltransferase) and H3K79 methylation in normal ovarian tissues and ovarian tumors and to explore the function of DOT1L and its underline mechanisms in ovarian cancer. Methods The expression of DOT1L and H3K79 methylation in 250 ovarian tumor samples and 24 normal ovarian samples was assessed by immunohistochemistry. The effects of DOT1L on cell proliferation in vitro were evaluated using CCK8, colony formation and flow cytometry. The DOT1L-targeted genes were determined using chromatin immune-precipitation coupled with high-throughput sequencing (ChIP-seq) and ChIP-PCR. Gene expression levels were measured by real-time PCR and immunoblotting. The effects of DOT1L on tumor growth in vivo were evaluated using an orthotopic ovarian tumor model. Results DOT1L expression and H3K79 methylation was significantly increased in malignant ovarian tumors. High DOT1L expression was associated with International Federation of Gynecology and Obstetrics (FIGO) stage, histologic grade, and lymphatic metastasis. DOT1L was an independent prognostic factor for the overall survival (OS) and progression-free survival (PFS) of ovarian cancer, and higher DOT1L expression was associated with poorer OS and PFS. Furthermore, DOT1L regulates the transcription of G1 phase genes CDK6 and CCND3 through H3K79 dimethylation; therefore, blocking DOT1L could result in G1 arrest and thereby impede the cell proliferation in vitro and tumor growth in vivo. Conclusions Our findings first demonstrate that DOT1L over-expression has important clinical significance in ovarian cancer and also clarify that it drives cell cycle progression through transcriptional regulation of CDK6 and CCND3 through H3K79 methylation, suggesting that DOT1L might be potential target for prognostic assessment and therapeutic intervention in ovarian cancer.